2016
DOI: 10.1186/s12939-016-0439-0
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in health behaviors among Brazilian adults: National Health Survey, 2013

Abstract: BackgroundConsidering the high socioeconomic inequalities prevailing in Brazil and lifestyle as a strong determinant of morbidity and premature mortality, our purpose was to evaluate the degree of socioeconomic disparities in the prevalence of health behaviors among Brazilian adult population using data from the 2013 Brazilian National Health Survey.MethodBased on a sample of 49,025 individuals aged 20 to 59 years, we estimated the prevalence of several health behaviors and a score of unhealthy behaviors accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 51 publications
4
47
0
9
Order By: Relevance
“…Studies analyzing individual behaviors have found healthier eating habits, such as adequate fruit and vegetable consumption, to be more prevalent among women than in men [41], but adherence to physical activity recommendations were more prevalent in men than in women [42]. In line with the above, in this study “ Snack DP ” mean scores adjusted for age and energy intake were significantly higher in men than in women.…”
Section: Discussionsupporting
confidence: 77%
“…Studies analyzing individual behaviors have found healthier eating habits, such as adequate fruit and vegetable consumption, to be more prevalent among women than in men [41], but adherence to physical activity recommendations were more prevalent in men than in women [42]. In line with the above, in this study “ Snack DP ” mean scores adjusted for age and energy intake were significantly higher in men than in women.…”
Section: Discussionsupporting
confidence: 77%
“…Since 2006, a national system has monitored risk factors for NCDs through telephone interviews 49 . In 2013, the National Health Survey showed that older age, less schooling, and the male sex were associated with less physical activity, prevalence of daily smoking, and low consumption of fruits and vegetables—highlighting the increased potential risk for this demographic 52, 53…”
Section: Discussionmentioning
confidence: 99%
“…Esto puede estar asociado a que los conceptos de sedentarismo e inactividad física hasta una década atrás eran utilizados como sinónimos, lo que podría explicar la poca evidencia de estudios que reporten el tiempo que pasan las personas frente a un computador, en trabajos de oficina o en actividades de tiempo libre, como jugar videojuegos y ver televisión, en Latinoamérica 1,28 . En Brasil, la ENS-2013 reportó que 67,5% de la población adulta es inactiva en su tiempo libre y, al igual que en Chile, las mujeres son más sedentarias que los hombres 29 . Otra investigación realizada en adultos brasileños identificó que los individuos pertenecientes a los grupos socioeconómicos más altos y con un mayor nivel educacional presentan puntajes sedentarios más altos, tal como se identificó en este estudio a nivel nacional 30 .…”
Section: Discussionunclassified